STARTUP E-COMPLAINT DENGAN INTEGRASI API UNTUK AKSES TANPA UNDUH PADA ONLINE SHOP - Indah Nur Setiani; Hana Fitri Anisa N W; Jeni Sundari (Universitas Islam Sumatera Utara, 2024)
The development of the times that demands everything to be more efficient and effective has prompted various companies to develop their online systems. Along with global trends, online shopping in Indonesia is also becoming more popular. Customer satisfaction in online shopping is a determining factor in their decision to make a repeat purchase. Dissatisfaction can increase customer turnover and the cost of acquiring new customers. A common problem faced by businesses is the quality of customer service, especially in handling complaints manually which is no longer relevant in the midst of technological developments. This research aims to create an online customer complaint system that facilitates the handling of complaints efficiently, and simplifies the administration of reports and documentation. The system uses API technology to ensure an effective interface for admins and customers. The Waterfall method is used in the development of this application to minimize bugs and detect errors. The results of the study show that a web-based complaint application that is connected to a mobile application in real-time can provide ease of access and increase customer trust in online shop services.